Preparation and characterization of immunopeptides isolated from pig spleen and evaluation of their immunomodulatory properties in vitro and in vivo - Xia, Minhao; Ling, Chong; Ye, Hui; Liang, Shujie; Cao, Qingyun; Wang, Weiwei; Zhang, Changming; Dong, Zemin; Tian, Min; Zuo, Jianjun; Zhu, Yongwen (Frontiers in Immunology, 2025)
The importance of small bioactive peptides derived from pig spleen have been used to enhance immune responses and support intestinal health. However, there is a lack of information regarding the conformational relationship and their effects on immune function of pig spleen proteins (PSPs). The objective of this study was to prepare and assess the immunomodulatory characteristics of immunopeptides from PSP. Firstly, enzymatic hydrolysates from PSP were prepared using alkaline protease and aminopeptidase, and small hydrolysate fractions with a <3 kDa were separated by SDS-PAGE and GPC. The bioactive peptides were then identified at peaks 5 to 7 (PSP-5, 6 and 7) by HPLC and TOF-MS, which were mainly composed of Pro-Glu-Leu by LC-MS. The PSP-5 and PSP-6 pronounced greater beneficial effects on cell viability and nitric oxide (NO) production than PSP-7 in macrophage, and PSP-5 exhibited a higher immunomodulatory ability than PSP-6. In vivo, the oral administration of 25-50 mg PSP-5/kg body weight (BW) protected against cyclophosphamide (CTX)-induced immunosuppression in spleen and intestine of mouse, as evidenced by increased cytokine and sIgA productions. In conclusion, a novel set of bioactive immunopeptides derived from PSP through enzymatic hydrolysis could enhance immunomodulatory properties.